2021
DOI: 10.1111/rode.12748
|View full text |Cite
|
Sign up to set email alerts
|

Son‐biased fertility stopping, birth spacing, and child nutritional status in Pakistan

Abstract: In this article, we append information from four cross-sectional household surveys (Multiple Indictors Cluster Survey of the United Nations International Children's Emergency Fund) in Punjab, Pakistan, collected between 2007 and2018 to create a data set of 140,000-150,000 child-level observations. Using linear regression, we document a strongly negative birth-order gradient in the nutritional status (measured as height-for-age z-scores) of children below age 5, indicating a pattern of disinvestment in later-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Reflecting earlier studies, they concluded that families strive for the desired mix of boys to girls through differential stopping behavior—that is, by continuing to bear children until the desired number of boys and girls is reached. This important conclusion from birth data is supported by other studies showing a steep birth‐order gradient in child nutritional status (Chaudhry, Khan, and Mir 2021), a phenomenon also observed in other South Asian populations with strong son preference (Jayachandran and Pande 2017).…”
Section: Propensity To Receive Remittancessupporting
confidence: 79%
“…Reflecting earlier studies, they concluded that families strive for the desired mix of boys to girls through differential stopping behavior—that is, by continuing to bear children until the desired number of boys and girls is reached. This important conclusion from birth data is supported by other studies showing a steep birth‐order gradient in child nutritional status (Chaudhry, Khan, and Mir 2021), a phenomenon also observed in other South Asian populations with strong son preference (Jayachandran and Pande 2017).…”
Section: Propensity To Receive Remittancessupporting
confidence: 79%
“…For Pakistan, persistent annual growth in population, which has been accompanied by many development issues, is often linked to high levels of fertility. Despite sustained efforts to reduce fertility, including the introduction of a national family planning initiative that dates back to the 1960s, the average fertility rate remained above six children per woman for several decades (Robey, 1991) until more recently, when this declined to an average of 3.8 births per woman (Chaudhry et al, 2021;Hardee & Leahy, 2008). We examined if Pakistan's nation-wide social security program, the BISP, has contributed to increasing fertility.…”
Section: Discussionmentioning
confidence: 99%
“…First, our evidence is for the BISP, which is the largest social protection program in South Asia, and the flagship program of Pakistan. Besides the scale of the BISP of being different from the Zambian Child Grant Programme, the focus on Pakistan is unique and likely to yield different results given the dynamics around fertility which includes sociocultural preference for male offspring (Chaudhry et al., 2021), and religious opposition to family planning (Ataullahjan et al., 2019). Second, we also contribute to the theoretical literature on the relationship between cash transfers and fertility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatedly, sons (especially eldest sons) in traditional societies are perceived as the source of old-age support for parents and play keys roles in inheritance and religious practices, contributing further to gender gaps in schooling (Hannum et al, 2009; Kaul, 2018). 3 Son bias in Pakistan increases fertility in families, since many couples continue having children until the desired number of sons is reached (Chaudhry et al, 2021; Hafeez & Quintana-Domeque, 2018). In this way, consanguineous marriage matches may be easier to find for women from families with a high degree of son preference.…”
Section: Literature Reviewmentioning
confidence: 99%